Discriminative treatment policy and constitutional rights violation of former PKI political prisoners and their families during the New Order in Indonesia - Wawan Susilo; Azis Setyagama (Studia Humanitatis)
The events of 1965 related to the suppression of “The Thirtieth of September Movement” and the prohibition of the Indonesian Communist Party (PKI) were a very heart breaking tragedy for the journey of national and state life in Indonesia. Hundreds of thousands and even millions of lives became victims of these events. The tragedy created a deep trauma for the Indonesian nation. The authoritarian regime of the New Order Regime implemented discriminatory policies against political prisoners who were members of the PKI and their families, who were considered traitors to the nation and state. This policy was set forth in the form of laws and regulations that violated the rights of former political prisoners and their families. The paper is a normative legal research that examines the legal rules issued by the New Order regime which shackled the constitutional rights of Indonesian citizens who were involved in “The Thirtieth of September Movement”, both the rebels and their families. The results of this study indicate that the discriminatory policies carried out by the Government in the New Order regime against former PKI political prisoners and their families were violations of human rights and were not in accordance with the Indonesian Constitution.